(untitled) (Research, Society and Development, 2021)
Objective: to analyze the use of long-term central venous catheters in adolescents with onco-hematological diseases, treated in the period between 2008 and 2018, in a specialized ward of comprehensive care for adolescent health. Method: Cross-sectional, retrospective, documentary analysis study with a quantitative approach, developed at a University Hospital in the State of Rio de Janeiro, Brazil. Results: Sample consisting of 49 forms on the clinical conditions of adolescents with onco-hematological diseases submitted to the implantation of central venous catheters. 65% (n = 32) were male with a minimum and maximum age of 12 and 19 years old, with 22.45% (n = 11) aged 15 years. As for onco-hematological diseases, leukemias predominated, especially acute lymphoid leukemia, represented by 43% (n = 21) of the cases, followed by lymphomas in 35% (n = 17). Among the types of devices, there was a predominance of the Peripherally Inserted Central Catheter in 71.43% (n = 35), and among the reasons for catheter removal, the absence of records prevailed in 51.02% (n = 25), followed by obstruction and infection, both with 12.24% (n = 6). Regarding the length of stay, it was noted that of the 49 catheters implanted, 55.10% (n = 27) had no records and 36.74% (n = 18) remained for less than one year. Conclusion: The evidenced data reinforce the need for nursing records and the application of good practices for the maintenance and handling of these catheters. Emphasis is placed on the importance of training the nursing team in order to promote patient safety through qualified nursing care.